Local epidemiology of the wood decay agent Laetiporus sulphureus in carob stands in Sicily. Issue 3 (28th January 2018) - Sillo, F.; Gianchino, C.; Giordano, L.; Mari, M.; Gonthier, P.
Summary: The basidiomycete Laetiporus sulphureus (Bull) Murrill is a forest pathogen causing brown cubical heart rot in a broad range of host trees. Despite its wide distribution and importance, studies aimed at understanding the epidemiology of the fungus in specific areas or hosts are lacking. In this study, an incidence of L. sulphureus as high as 34% was determined through molecular analysis of wood samples collected from 70 carob ( Ceratonia siliqua L.) trees in the South‐west of Sicily, Italy. A phylogenetic analysis of Internal Transcribed Spacer (ITS) sequences indicated that all carob isolates belonged to the cluster E of Laetiporus taxonomy. Ten molecular markers based on Single Sequence Repeats (SSRs) designed on the L. sulphureus genome were developed, and isolates were genotyped through High‐resolution Melting (HRM) analysis. High gene diversity (0.581), no correlation between fungal genotype and host tree species and significant correlation between spatial and genetic distance were observed, suggesting an important role of basidiospores in the epidemiology of the fungus and a risk of transmission from a host tree species to the others. Finally, from a prognostic perspective, significant differences among isolates in terms of mycelial growth suggest that in addition to an accurate identification, a phenotypic characterization of isolates affecting trees may also be important.